Chronic Actinic Dermatitis with Leonine Facies and Iatrogenic Adrenal Insufficiency Successfully Treated with Topical Tacrolimus - Ploysyne Busaracome; Penpun Wattanakrai; Natta Rajatanavin (Karger Publishers, 2011)
Chronic actinic dermatitis is a chronic photosensitivity disorder characterized by severe eczematous lesions on sun-exposed skin areas. We report a case of chronic actinic dermatitis presenting with leonine facies and secondary adrenal insufficiency, which was successfully treated with topical tacrolimus. The facial lesions dramatically improved after sun avoidance and topical tacrolimus application. After almost 20 years of oral corticosteroid therapy complicated with secondary adrenal insufficiency, we were able to switch treatment from systemic corticosteroids to topical tacrolimus to control the patient's symptoms.